Abnormal Liver Function in Predicting COVID-19 Patients’ Prognosis - Sari, Sakinah Rahma; Kurniawan, Juferdy (UI Scholars Hub, 2022)
Despite of the high prevalence of liver enzyme elevation in COVID-19 patients, its effect on predicting COVID-19 patients’ prognosis was still debatable. This evidence-based case report aims to evaluate the effect of abnormal liver function in the prognosis of COVID-19 patients. Literature searching was performed on August 16-17 2021 using 3 databases: PubMed, Scopus, and Proquest. The articles selected by title/abstract screening, duplication elimination, and applying eligibility criteria were then appraised using Centre of Evidence Based Medicine (CEBM), University of Oxford. Some of the studies reported there were no significant difference in the prognosis of COVID-19 patient with and without abnormal liver function. However, most of the studies reported abnormal liver function as an independent poor prognosis predictor in COVID-19 patients. Based on the study with the highest level of evidence, the elevation of AST and ALT increase the risk of poor prognosis in COVID-19 patients [OR 2.98 (95% CI 2.35-3.77), p<0.0001) and OR 1.73 (95% CI 1.32-2.27, p<0.001)]. Based on the 34 studies appraised, we conclude that abnormal liver function will increase the risk of poor prognosis in COVID-19 patients. Thus, careful monitoring must be done in COVID-19 patients with abnormal liver function.